New Laplace and Helmholtz solvers - Gopal, A; Trefethen, L (National Academy of Sciences, 2019)
Numerical algorithms based on rational functions are introduced that solve the Laplace and Helmholtz equations on 2D domains with corners quickly and accurately, despite the corner singularities.